Analisis Business Intelligence Ulasan Negatif Aplikasi M-Pajak Menggunakan BERTopic untuk Evaluasi Layanan Digital - Henry Pandia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The M-Pajak application is part of the government’s digital tax service transformation aimed at improving the efficiency and accessibility of tax services for the public. However, user complaints on the Google Play Store indicate that technical and operational problems persist with the application. This study aims to analyze negative user reviews of the M-Pajak application using BERTopic to generate Business Intelligence insights related to the quality of government digital tax services. BERTopic was selected because it uses transformer-based contextual embeddings, which are well-suited to analyzing short, unstructured, and informal mobile application reviews, thereby helping identify complaint themes in a more context-aware way than traditional word-distribution-based topic modeling approaches. The data were collected from Google Play Store reviews from May 2023 to May 2026, totaling 6,024 user reviews. A total of 5,008 negative reviews with ratings of 1 or 2 were used as the primary focus of the analysis. The research stages included data scraping, preprocessing, BERTopic modeling, topic evaluation, and Business Intelligence interpretation. The results show that the main user problems are related to authentication and login, system errors, email and OTP verification, NPWP and NIK registration, and digital service stability. Model evaluation yielded a Topic Coherence score of 0.522, a Topic Diversity score of 0.667, and a Topic Quality score of 0.348, indicating that the topic quality was moderate yet interpretable. The contribution of this study lies in utilizing negative reviews of a digital tax service application as a source of operational insights to support the evaluation and improvement of government digital public services.